Modeling dynamics of HIV infected cells using stochastic cellular automaton - Monamorn Precharattana (2018)
Ever since HIV was first diagnosed in human, a great number of scientific works have been undertaken to explore the biological mechanisms involved in the infection and progression of the disease. Several cellular automata (CA) models have been introduced to gain insights into the dynamics of the disease progression but none of them has taken into account effects of certain immune cells such as the dendritic cells (DCs) and the CD8+T lymphocytes (CD8+T cells). In this work, we present a CA model, which incorporates effects of the HIV specific immune response focusing on the cell-mediated immunities, and investigate the interaction between the host immune response and the HIV infected cells in the lymph nodes. The aim of our work is to propose a model more realistic than the one in Precharattana et al. (2010) [10], by incorporating roles of the DCs, the CD4+T cells, and the CD8+T cells into the model so that it would reproduce the HIV infection dynamics during the primary phase of HIV infection. © 2014 Elsevier B.V. All rights reserved.